The Role of Bhabinkamtibmas in Resolving Community Disputes Through Focus Group Discussion in the Jurisdiction of the Talun Polres Police Blitar - Tesalonika, Tesalonika (Advances in Police Science Research Journal, 2024)
Disputes that frequently occur in the community can disrupt the maintenance of public security and order. The Focus Group Discussion (FGD) activity can be used by Bhabinkamtibmas (community police officers) as a way to communicate with village officials and the surrounding community to prevent disturbances to public security and order. This research aims to describe the role of Bhabinkamtibmas in resolving community disputes through FGD within the jurisdiction of Talun Police Station, Blitar Police Department, and to understand the impact of the FGD activities conducted by Bhabinkamtibmas on improving the relationship between the community and Bhabinkamtibmas in the Talun Police jurisdiction. This study uses conceptual literature, including the concepts of Bhabinkamtibmas, FGD, resolving community disputes, role theory, social interaction theory, and communication theory. The research applies a qualitative approach with field research. Data collection techniques include interviews, observations, and document studies. Data validity is ensured through data triangulation. The data analysis technique involves data collection, data reduction, data presentation, and verification. The research findings indicate that some Bhabinkamtibmas officers are less active and less knowledgeable about their material but are supported by an active community in expressing their aspirations. The role of Bhabinkamtibmas accommodates the dimension of conflict prevention. Bhabinkamtibmas builds a trust-based relationship that facilitates early detection and prevention of future conflicts. The role of Bhabinkamtibmas in resolving community disputes through FGD has an impact on village officials, as they become more actively involved in addressing community issues in their respective areas. The role of Bhabinkamtibmas in resolving community disputes through FGD in the Talun Police jurisdiction is considered effective and proactive.